Habituasi Toleransi sebagai Upaya Menguatkan Pendidikan Anti Bullying di Sekolah - Ni'mah, Zetty (Peradaban Journal of Interdisciplinary Educational Research, 2024)
Cases of bullying have been deeply concerning in schools or even Islamic schools. Educational institutions, which should be safe and comfortable places for learning, have unfortunately become hellish and traumatic places remembered as painful scars by the victims. This article explores the importance of instilling the character of tolerance as an effort to address bullying in educational institutions. Programs such as child-friendly schools and the internalization of tolerance through school programs are key to building an inclusive school culture that respects diversity. The process of internalizing the character of tolerance in schools can be done by referring to the theory of social construction, through externalization, objectification, and internalization. Instilling attitudes of tolerance in the context of anti-bullying can be done in various ways, including character development programs, anti-bullying movements, integration with school culture, integration into curriculum and school self-development programs, as well as building communication and cooperation with parents. With a comprehensive and integrated approach, instilling the character of tolerance can be one of the effective solutions to address bullying in educational institutions. Kasus bullying sudah sangat memprihatinkan terjadi di sekolah atau madrasah bahkan pesantren. Lembaga Pendidikan yang seharusnya menjadi tempat aman dan nyaman untuk menimba ilmu harus berbanding terbalik menjadi neraka dan tempat traumatik yang diingat sebagai luka menyakitkan oleh para korban. Artikel ini mengeksplorasi pentingnya pembiasaan karakter toleransi sebagai upaya mengatasi bullying di lembaga pendidikan. Program-program seperti sekolah ramah anak dan internalisasi karakter toleransi melalui program-program sekolah menjadi kunci dalam membangun budaya sekolah yang inklusif dan menghormati keberagaman. Proses internalisasi karakter toleransi di sekolah dapat dilakukan dengan mengacu pada teori konstruksi sosial, melalui eksternalisasi, obyektifikasi, dan internalisasi. Pembiasaan sikap toleransi dalam konteks anti bullying bisa dilakukan melalui berbagai cara, termasuk program pengembangan karakter, gerakan anti bullying, integrasi dengan budaya sekolah, integrasi dalam program pembelajaran dan pengembangan diri sekolah, serta membangun komunikasi dan kerjasama dengan orang tua. Dengan pendekatan yang komprehensif dan terintegrasi, pembiasaan karakter toleransi dapat menjadi salah satu solusi efektif dalam mengatasi bullying di lembaga pendidikan.